Diseño de un plan de comunicación interna para la oficina matriz del Consejo Nacional Electoral (CNE) en Quito - Enríquez Vinueza, Diana Cristina (2015)
Communication is an important element for organizations that properly applied allow healthy flow of information besides supporting compliance management processes, and, because of that, they have a positive impact on the corporate identity and the work climate. Today, with technological advancement, they will feature a number of channels which support the process either from the internal and external network. The research methodology consisted of an exploratory and descriptive study. The study method was deductive. Historical, documentary and descriptive research was used. A field study was conducted at the Consejo Nacional Electoral, which allowed knowing some weaknesses in the communication process, such as: communication with superiors, sources of formal information, knowledge about internal communication procedures, weak communication up, among others that have affected the corporate identity and the working environment. The technique used was a survey using a structured questionnaire. As a result the lack of an internal communication plan was evident in the institution, which is affecting the working environment and socialization of corporate culture. From this context, Internal Communication Plan, focused on constitute a tool that supports the flow of communication in the institution, and thus promote corporate culture as well as an impact on improving the working environment of the entity set. The internal image was also diagnosed and improvement strategies were proposed.